The mobile life of women between neighborhoods and cities: anthropological explorations in the urban borders of the metropolitan region of Belo Horizonte (Minas Gerais, Brazil) - Vidal e Souza, Candice (Editorial Pontificia Universidad Javeriana, 2018)
The article presents the preliminary results of an anthropological research carried out in two neighborhoods of the metropolitan region of Belo Horizonte. There, displacements are analytically described as movement practices located in the social space, which act against the effects of gender and residence in the journeys of subjects in the cities. The neighborhoods of Jardim Canada and Água Limpa are located along highway BR-040, where there are housing and utilities for middle class and lower income groups. In this heterogeneous context of urban expansion, the focus is on the mobility of women and their families, who migrated from other places and now make routine trips to fulfill work and personal service responsibilities. The mobility practices are thought in relation to the metropolitan context and the changes in valuation associated with the movement, leading to a search of a better life and the city that could be, intertwining the trajectories of individuals to the space-time of the urban borders.